The evolution of allergen‐specific immunotherapy: The near and far future. (24th November 2020) - Pajno, Giovanni Battista; Passanisi, Stefano; Valenzise, Mariella; Messina, Maria Francesca; Lombardo, Fortunato
Abstract: In the era of precision medicine, allergen immunotherapy (AIT) represents a landmark for the management of IgE‐mediated allergic diseases. AIT is recognized as a potentially curative therapy and is currently accepted and routinely prescribed worldwide. However, there are still unmet needs. The efforts of researchers are aimed at implementing current immunotherapeutic strategies to improve the standard care of patients suffering from IgE‐mediated respiratory allergic diseases. In addition, over the horizon, the most realistic option is the active treatment of IgE‐mediated food allergy with oral immunotherapy. Preclinical studies and clinical trials are increasingly conducted to identify innovative forms of AIT administration, potential biomarkers, alternative immunotherapeutic allergen candidates, and new adjuvants. Telemedicine could represent a further emerging field capable of supporting health service delivery and improving clinical outcomes of AIT.